Using Concept Maps in Teaching Arabic as a Foreign Language - Yusuf Ceylan; Senem Ceylan (Şarkiyat Mecmuası)
Today’s understanding of education shows that the constructivist paradigm, which focuses on high-level thinking skills, emphasizes cognitive processes, and is based on meaningful learning, has replaced the mechanical, passive, individual, and rote learning approach of behavioral learning theory. The change in the educational and scientific point of view regarding the learning and teaching processes of foreign language teaching makes itself felt more each day. Accordingly, this article discusses the role of the teacher and the student in teaching Arabic and the applied methods within the framework of new techniques, and explains the use of new methods and techniques and how they have become widespread alongside the traditional ones. Although the acquisition of language skills varies from student to student in foreign language teaching, more positive results are known to obtained from well-structured teaching. The use of various methods and techniques for acquiring basic and secondary language skills has great importance in terms of addressing different areas of intelligence and minimizing individual differences. Providing students with a cognitive, affective, and visually supported learning environment makes a significant difference in terms of holistic learning. The process learners undergo to construct knowledge is highly dependent on previous knowledge and concepts. In this respect, using concept maps to teach the concepts of a subject area plays an important role in realizing meaningful learning. Concept maps facilitate the construction of learning in the mind by showing the relationships between concepts and embodying their ties with other concepts in the same category through figures or words. Concept maps are also effective at minimizing learners’ misconceptions. This study will discuss how concept maps can be used as a method for teaching Arabic grammar subjects. After introducing the constructivist theory on which the concept maps method is based, the article will then focus on the relationship between meaningful learning and concept maps and evaluate the contributions concept maps make to acquiring the basic concepts in Arabic grammar and to having students effectively learn the relationships between concepts. In addition, the article will provide application examples that can be used with regard to the types of concept maps that are frequently used, especially in preparatory classes.